Analysis of SReits in a world of uncertainty (hospitality, healthcare, industrial, new economy) - Yu, Junjie (Nanyang Technological University, 2024)
This abstract presents a thorough examination of Singapore Real Estate Investment Trusts (SREITs), categorized using three primary methods: Fundamental, Technical, and News analysis.